2015
DOI: 10.9734/bjmmr/2015/16344
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Pattern of Osteoarthritis at Ogbaku, Imo State University Teaching Hospital Annex, Mbaitoli Local Government Area, Imo State, Southeast, Nigeria

Abstract: This work was carried out in collaboration between all authors. Author SNU designed the work and wrote literature review/discussion. Author TNU collected raw data. Author LCI performed proof reading and partial funding. Author ACOO helped in literature review and partial funding. Author NRU typed the manuscript. Author JE co-ordinated the collection of data. Author CUO managed statistical analysis. Author EAA facilitated the collection of raw data. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous studies have identified "Ember months", that is, the last four months of the year (Ukibe et al, 2011;Omobowale et al, 2011) as the most critical period while other studies pointed out to holiday periods (Anowar et al, 2021) while others argued in favour of holiday periods (National Safety Council (2023) or specifically festive periods (Oyenuga et al, 2006). This paper considered all the suggested periods and tested for the difference in the RTA cases during Festive Holiday, Non-holiday, and Non-Festive Holiday and found a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have identified "Ember months", that is, the last four months of the year (Ukibe et al, 2011;Omobowale et al, 2011) as the most critical period while other studies pointed out to holiday periods (Anowar et al, 2021) while others argued in favour of holiday periods (National Safety Council (2023) or specifically festive periods (Oyenuga et al, 2006). This paper considered all the suggested periods and tested for the difference in the RTA cases during Festive Holiday, Non-holiday, and Non-Festive Holiday and found a statistically significant difference.…”
Section: Methodsmentioning
confidence: 99%
“…(9,10) In the present study the prevalence of OA increased with age as maximum number of patients were seen in 71-80 years age group as compared to studies by Shadab et al, majority, 199 patients were above 60 years (11) and Ukibe et al, 34% of the OA patients were in 64-75 year age group. (4) In a study by Patil S et al 33% of the patients were more than 60 years. (12) OA is more common in female patients in present study (66%) as compared to the studies by Ukibe et al (34%), Shadab et al (61.54%), Patil PS et al (65.7%) and Radha et al (66%).…”
Section: Gendermentioning
confidence: 97%
“…(12) OA is more common in female patients in present study (66%) as compared to the studies by Ukibe et al (34%), Shadab et al (61.54%), Patil PS et al (65.7%) and Radha et al (66%). (4,11,12,13) OA strikes women more than men and it increases in prevalence, incidence and severity after menopause. (14) Data from Women's Health initiative showed that, women on oestrogen replacement therapy was 15% less likely to require Total Knee or Hip arthroplasty than those not taking such therapy.…”
Section: Gendermentioning
confidence: 99%
See 2 more Smart Citations